Can someone please help me ASAP? Please show work. It’s due today!
I will give brainliest if it’s correct!
![Can someone please help me ASAP Please show work Its due today I will give brainliest if its correct class=](https://us-static.z-dn.net/files/dec/80eef2fa891bccb8489bed1110b83ce8.png)
Answer:
B second choice
Step-by-step explanation:
2x - y = 2
6x + 3y = -18
The first step is to solve one equation for one variable.
He chose to solve the first equation for y:
2x - y = 2
-y = 2 - 2x
y = -2 + 2x
So far, Robert is correct. He solved the first equation correctly for y.
The second step is to substitute what y equals into the other equation.
6x + 3y = -18
6x + 3(-2 + 2x) = -18
6x - 6 - 6x = -18
-12x = -12
x = -1
Now we substitute -1 for x in the equation y = -2 + 2x.
y = -2 + 2x
y = -2 + 2(-1)
y = -2 - 2
y = -4
The correct solution is (-1, -4).
Robert's mistake was to substitute into the incorrect equation.
Answer: B second choice
Answer:
B second choice
Step-by-step explanation:
Step-by-step explanation:
2x - y = 2
6x + 3y = -18
The first step is to solve one equation for one variable.
He chose to solve the first equation for y:
2x - y = 2
-y = 2 - 2x
y = -2 + 2x
So far, Robert is correct. He solved the first equation correctly for y.
The second step is to substitute what y equals into the other equation.
6x + 3y = -18
6x + 3(-2 + 2x) = -18
6x - 6 - 6x = -18
-12x = -12
x = -1
Now we substitute -1 for x in the equation y = -2 + 2x.
y = -2 + 2x
y = -2 + 2(-1)
y = -2 - 2
y = -4
The correct solution is (-1, -4).
Robert's mistake was to substitute into the incorrect equation.
Answer: B second choice